Effect Of Incorporation Of Drumstick (Moringa Oleifera) Leaves Extract On The Qualityof Ground Chicken Nuggets - Gomkale, A P; Sakunde, Deepali T; Kadam, B R; Mane, D V; Durala, D (Journal of Meat Science, 2023)
The present study was conducted to optimize the level of incorporation of drumstick (Moringa oleifera) leaves extract in ground chicken nuggets. The aqueous MoLE was prepared by taking dried mature Moringa olifera leaves powder and water at 1: 10 ratio, then kept at 55ºC for 3 hours and finally filtered with the help of filter paper. During optimization, ground chicken nuggets were prepared by incorporating 0, 2.5, 5, and 7.5% MoLE in the nugget mix. The quality and acceptability of the MoLE added nuggets were evaluated based on proximate composition, physico-chemical, and sensory analysis. Moisture and fat showed a non-significant difference, while protein and ash significantly increased to 5% MoLE added product. pH decreases while cooking yield & emulsion stability increase non-significantly with an increase in the level of MoLE. Sensory scores of flavour, texture, juiciness and overall acceptability were comparable in the 2.5 % MoLE, while appearance was affected non significantly by the increased level of MoLE. The result of the study shows that nuggets incorporated with a 2.5% level of MoLE were comparable to the control in all quality parameters, along with improved nutritional properties.